An Examination of Technology Acceptance to Sales Increase Through Marketplace in Bandar Lampung - Destiana; Jufri Yandes; Dwi Rahmawati; Syarif Fadillah (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2024)
The Covid-19 pandemic is a global outbreak that has significantly impacted all aspects of life. The occurrence of various policy changes and the emergence of uncertainty pose a threat to MSMEs. Besides that, there are also changes in consumer lifestyle patterns that refer to the lifestyle of staying at home, creating a sense of empathy and social solidarity, switching to digital media, and consumers changing from the top of the pyramid (self-actualization and respect) to the bottom need for food. Based on these changes, MSMEs need to take appropriate steps that can be used as opportunities. Technology acceptance and adoption of marketplace applications are steps that can be taken to maintain sales levels. This research aims to test the acceptance of technology to increase sales through marketplace applications. This research was conducted in Bandar Lampung City by distributing questionnaires in a Google form to 95 Banana Chip MSMEs who had used the marketplace application. This type of research is descriptive quantitative using purposive sampling techniques. Then, the data that has been obtained is processed using SmartPLS 3.0. The results of this research show that technology acceptance has a significant effect on marketplace applications with a P-Value of 0.000, marketplace applications have a substantial effect on sales levels with a P-Value of 0.000, but technology acceptance has no significant impact on increasing sales with a P-Value of 0.311 and technology acceptance has a substantial effect towards growing sales through the use of marketplace applications with a P-Value of 0.000.